(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Joketro Village, Parang District is one of the villages in Magetan Regency, East Java, where most of the people make a living as producers and sellers of traditional herbal medicine. From generation to generation, this herb is a legacy from our ancestors which is preserved and beneficial for the health of the human body. Currently, these herbs are only produced on a small scale and are only sold by going door to door. The Universitas PGRI Madiun community service aims to help improve the herbal medicine business. The methods used include: 1) we donated PIR sensor-based automatic grater machines, and 2) provided assistance and training in the use of tools for herbal medicine entrepreneurs with the aim of increasing herbal medicine production. The result of mentoring is that herbal medicine entrepreneurs have the skills to use machine technology to increase the quantity of herbal medicine produced. By increasing herbal medicine production, it will certainly improve the community’s economy, especially herbal medicine entrepreneurs in Joketro Village.